Rejection Of Perda Zakat In East Lombok: Public Criticism On Public Policy - Ahmad Fathan Aniq (Ulumuna, 2007)
One of five Islamic pillars is zakah, which aims to create social welfare. As the last revealed religion, Islam puts the social justice in a high sequence. As the matter of fact, the word “adl”, “qisth”, and “mizan” as well as their derivates, are the third most frequently mentioned word after the word “Allah” and knowledge respectively in al-Qur’an. This article is all about the development of zakah regulation in Indonesia, particularly in East Lombok. Perda Zakat in East Lombok was enacted by its regent, Ali bin Dahlan, by a Decision Letter No. 4 of 2004 as the implementation of Regional Regulation No. 9 of 2002 on Zakâh and Prohibition to Drink Alcoholic Drink. Therefore, he was enthusiastic to apply the regulation by deducting the public servants’ salaries of 2.5% every month. But most of Muslim teachers refused the regulation. For them, the regulation contradicted with zakâh concept in Islam.